A Paradigm Shift Toward Zero Accident - Soltani, Amirmasoud (Cranfield University, 2017)
Presented at the "Future of Transportation" World Conference, July 2017, Cologne, Germany.
Keywords: Autonomous Vehicles'; 'Intelligent Transportation Systems'; 'Mechatronics'; 'aritificial intelligent'; 'connected vehicles'; 'Automation and Control Engineering'; 'Automotive Mechatronics'; 'Autonomous Vehicles'; 'Automotive Engineering not elsewhere classified'; 'Transport Engineering'; 'Interdisciplinary Engineering not elsewhere classified'